Disruption of brightness discrimination in a shock avoidance task by phencyclidine and its antagonism in rats - Tang, A H; Franklin, S R (The Journal of pharmacology and experimental therapeutics, 1983)
Rats were trained to make a simultaneous brightness discrimination in order to avoid or escape foot shocks in an automated Y-maze. Brightness discrimination was completely disrupted by phencyclidine (PCP, 3 mg/kg), ketamine (30 mg/kg) and dexoxadrol (10 mg/kg). At these doses, there was increased locomotor activity between trials. The number of movement attempts to avoid shock during a trial were either unchanged or reduced. Several drugs with various clinical applications (chlorpromazine, haloperidol, diazepam, pentobarbital, d-amphetamine, propranolol, clonidine and prazosin) did not impair brightness discrimination in behavioral stimulant or depressant doses. The levoisomer of dexoxadrol, levoxadrol, was also inactive. Daily administration of PCP for 5 consecutive days produced progressive increases in locomotor stimulation with no tolerance to effects on brightness disruption. The disruption of brightness discrimination by PCP was not reversed by chlorpromazine, haloperidol, diazepam, propranolol or apomorphine at doses which reduced the locomotor stimulation by PCP. Both locomotor stimulation and discrimination disruption were blocked by prazosin and clonidine. A central adrenergic mechanism is implicated for some behavioral effects of PCP.